Antara Harapan dan Kehampaan: Teologi Eksistensial Pengkhotbah 9:1-6 dan Ambisi Manusia - Jane Isye Lambiombir (PT. Penerbit Tiga Mutiara, 2025)
Ecclesiastes 9:1-6 presents a fundamental and provocative theological statement about the reality of death as an inevitable fate for all humanity, without distinguishing between the righteous and the wicked. This discourse explicitly challenges the retributive ethical framework that assumes a linear relationship between morality and reward, while also revealing the existential absurdity of humans who often seek meaning through fragile worldly achievements. This study aims to interpret the pericope through an existential and contextual theological approach, focusing on its theological relevance in addressing the crisis of spirituality and ethics in modern culture dominated by ambition for power, economic exploitation, and the marginalization of transcendental values. Utilizing a reflective-critical hermeneutical method, this study argues that awareness of mortality should not lead to ontological despair, but rather serve as a starting point for forming a more authentic, relational, and ethical orientation to life. Death in this text functions as an epiphanic moment that unveils human limitations while reorienting existential focus toward God and social responsibility. The novelty of this research lies in its prophetic reading of a wisdom text that has often been interpreted pessimistically, highlighting its potential as a theological critique against modern nihilistic and anti-spiritual ideologies. This study contributes to the development of a contextual theological framework capable of constructively and transformatively responding to the crisis of meaning and ethics in contemporary society.